A decade of antimicrobial resistance trends in Pseudomonas aeruginosa: insights from a tertiary care hospital in Saudi Arabia (2013–2022) - Shabi, Yahya; Algarni, Abdullah; Al bshabshe, Ali; Alazraqi, Tarik; Patriquin, Glenn; Bawazeer, Abdulah OS; Mohammed, Safia Abdullah; Habbash, Sara; Somily, Ali; Alqahtani, Abdulah J.; Alhamhhum, Saeed M. S. (Frontiers in Microbiology, 2025)
BackgroundPseudomonas aeruginosa (PA) is a significant cause of nosocomial infections, and increasing antimicrobial resistance complicates management.ObjectivesTo characterize antimicrobial susceptibility trends, we conducted a retrospective study of PA clinical isolates over 10 years (2013–2022) at a tertiary care hospital in Saudi Arabia.ResultsA total of 2,490 PA isolates were analyzed (1,452 from general wards and 1,038 from ICUs). Carbapenem resistance was observed in 40% of isolates; 37.5% were multidrug-resistant (MDR), 5.3% were extensively drug-resistant (XDR), and 3.5% met the criteria for difficult-to-treat resistance (DTR).ConclusionThis study provides an overview of PA resistance pattern trends in Saudi Arabia and emphasizes the importance of establishing an antimicrobial stewardship program.